The importance of the production control method for mature model parameters of production control effects based on the conducted survey questionnaire - Dratwińska-Kania, Beata (Znaczenie metody kontroli produkcji dla stanowienia parametrów modelu dojrzałości efektów kontroli produkcji w świetle przeprowadzonych badań ankietowych, 2019)
The paper presents a model approach to production control. A maturity model was developed for production control effects, which is a tool to improve the current state in the desired direction. A survey questionnaire was also carried out to determine which type of control should be chosen to reinforce the model parameters (achieve a higher level of maturity). The research revealed that the model parameters indicate differentiation due to the choice of the control method. The respondents chose different methods of production control for individual parameters of the model. Based on the conducted research, the goal of the paper is to develop a maturity model of production control effects and assess the production control types in terms of adjusting to the maturity model parameters of the production control effects. The study adopted the literature review and a survey questionnaire as research methods. The considerations focus on the possibility of improving the maturity model parameters of production control effects by selecting an appropriate type of production control
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 19-28
Keywords: control; production control; maturity model; kontrola; kontrola produkcji; model dojrzałości